TECHNOLOGIES FOR DEVELOPING METHODOLOGICAL COMPETENCES OF PRESCHOOL TEACHERS IN INDIVIDUAL EDUCATION (World Bulletin of Education and Learning, 2025)
The article covers the theoretical and practical foundations of developing methodological competencies of future preschool teachers through an individual educational environment. The process of professional formation of a teacher is analyzed based on the concept of person-centered education. The importance of modern pedagogical technologies, innovative methods and digital platforms used in the direction of individual education is scientifically demonstrated.
Keywords: Individual education, methodological competence, person-centered approach, digital education, preschool education, professional development, interactive methods.